Enterprise Resource Planning Implementation Towards Improving Company Performance - Suryanto, Suryanto; Tyas, Ari Anggrani Winadi Prasetyoning (Jurnal Ilmiah Manajemen Kesatuan, 2024)
In this digital era, companies are required to adapt to rapid technological developments. One way that can be done is by implementing Enterprise Resource Planning (ERP). ERP is an integrated system that combines various business processes in one platform. Implementing ERP can help companies improve the efficiency and effectiveness of business processes, improve product and service quality, increase customer satisfaction, and increase company profits. This research aims to analyze digital transformation through the implementation of ERP at PT. Kobexindo Equipment. This research uses a descriptive method with a case study approach. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation. The research results show that the implementation of ERP at PT. Kobexindo Equipment has brought about significant digital transformation. This transformation can be seen from several things, including: increasing use of information technology in business processes, increasing data integration between departments, increasing automation of business processes, increasing access to information for employees. This digital transformation has had a positive impact on company performance. This can be seen from several indicators, including: increasing efficiency and effectiveness of business processes, increasing product and service quality. Increased customer satisfaction. Increased company profits. The findings of this research indicate that implementing ERP can be an effective way to carry out digital transformation and improve company performance.